The Politics of Race and Education: Second-Generation Laotian Women Campaign for Improved Educational Services - Shah, Bindi V. (Social justice, 2008)
Part of a special issue on Asian and Pacific Islander populations within the U.S. Despite often being conceptualized as either a model minority or at-risk refugees or foreigners, second-generation Laotian-American women are challenging these perceptions through community organization. In California's West Contra Costa County, the Asian Pacific Environmental Network (APEN) has sought to build an ethnic-specific program, the Laotian Organizing Project, which targets young teenage Laotian-American girls. Laotians are among the newest immigrants and their U.S. born children face a host of specific issues, including high rates of teen pregnancy, gang membership, and institutionalization in care facilities. The writer discusses APEN's efforts at mobilizing Laotian-American girls in Richmond High School, California.